Enhancing Early Reading Skills in Students with Learning Difficulties through Project-Based Multisensory Instruction - Basuki, Basuki; Purwanta, Edi (Papanda Publisher, 2025)
Early reading skills constitute fundamental cornerstones in children's academic development, yet significant proportions of elementary students encounter substantial barriers in mastering critical literacy competencies. This study investigated the effectiveness of project-based multisensory instruction in enhancing early reading skills among third-grade students with learning difficulties. This action research employed a qualitative approach using the Kemmis and McTaggart model with two implementation cycles. Twelve third-grade students with early reading difficulties at SDN 006 Rantau Pulung participated in the study. The intervention integrated visual, auditory, tactile, and kinesthetic modalities through plasticine manipulation and diorama creation activities. Data collection utilized reading ability tests, structured observations, and performance assessments across multiple literacy components including word reading, writing, creative expression, and storytelling capabilities. The intervention achieved remarkable success, with 100% of students reaching satisfactory performance levels by Cycle II, compared to 75% in Cycle I. Students who initially struggled most demonstrated the greatest improvements, with gains reaching up to 35.25%. The overall class average increased significantly by 9.15%, while performance variability decreased substantially (standard deviation reduced from 18.74% to 6.94%), indicating improved learning equity across the classroom. The findings provide compelling evidence that multisensory project-based approaches effectively address diverse learning needs in inclusive settings. The integration of concrete manipulatives with systematic literacy instruction successfully eliminated performance disparities while maintaining high engagement levels. The research contributes theoretical validation for asset-based approaches to learning difficulties and offers practical frameworks for implementing inclusive literacy instruction that accommodates diverse learning profiles in elementary education contexts.